2020
DOI: 10.3390/w12092523
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Gold Mining on the Water Quality in Monterrey, Bolívar (Colombia)

Abstract: Gold mining uses chemicals that are discharged into rivers without any control when there are no good mining practices, generating environmental and public health problems, especially for downstream inhabitants who use the water for consumption, as is the case in Monterrey township, where the Boque River water is consumed. In this study, we evaluate Boque River water quality analyzing some physicochemical parameters such as pH, heavy metals, Hg, and cyanide; bioassays (Lactuca sativa, Hydra attenuata, and Daph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The parish of El Dorado de Cascales is one of the areas with the highest mining activity in the northern Amazon region of Ecuador and, like other regions of the country such as the Andean [63] and Littoral [49,62] regions and other countries in the region [64][65][66], one of the main problems is the lack of control of mining activities by local, regional and national government authorities. The lack of employment and entrepreneurial opportunities makes people in these areas characterized by high gold concentrations to engage in this activity, so much so that there are even people from other regions and from neighboring Colombia who are tempted by this activity.…”
Section: Discussionmentioning
confidence: 99%
“…The parish of El Dorado de Cascales is one of the areas with the highest mining activity in the northern Amazon region of Ecuador and, like other regions of the country such as the Andean [63] and Littoral [49,62] regions and other countries in the region [64][65][66], one of the main problems is the lack of control of mining activities by local, regional and national government authorities. The lack of employment and entrepreneurial opportunities makes people in these areas characterized by high gold concentrations to engage in this activity, so much so that there are even people from other regions and from neighboring Colombia who are tempted by this activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several adverse effects on the health of mine workers [10] and the population surrounding mining sites have been described in the literature [11][12][13]. Examples of destructive health impacts include elevated rates of HIV/AIDS [14], endemic diseases such as malaria [15], mental health problems [16,17], and conditions triggered by environmental impacts such as toxic chemicals [18][19][20][21]. In addition, NREP sites often experience a high influx of migrants due to the creation of new jobs and secondary businesses [22,23].…”
Section: Of 21mentioning
confidence: 99%
“…They found that a significantly positive correlation between metal concentration and antioxidants catalase and superoxide dismutase was established, supporting the potential ecological risk as a result of heavy metals pollution in the River Kaduna. Martín et al evaluated the water quality of Boque River in Colombia contaminated by gold mining drainage by bioassays (Lactuca sativa, Hydra attenuata, and Daphnia magna), mutagenicity (Ames test), and microbiological assays, in addition to physiochemical parameters such as pH, heavy metals, Hg, and cyanide [12]. They found Hg, Cd, and cyanide exceeded the permitted concentrations in Colombia and D. magna showed sensitivity and L. sativa showed inhibition and excessive growth in the analyzed water.…”
Section: Overview Of This Special Issuementioning
confidence: 99%